PENGARUH MODEL PjBL BERBASIS BUKU DIGITAL DAN MINAT BELAJAR TERHADAP LITERASI SASTRA ANAK PADA SISWA KELAS IV SD NEGERI MOROSUNGGINGAN JOMBANG - Anis Saadah; Wawan Gunawan; Suhari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of a digital book-based Project-Based Learning model compared to a digital book-based lecture model, as well as learning interest, on children's literary literacy in fourth-grade students at Morosunggingan Elementary School, Jombang. The study used a quantitative approach with a two-by-two factorial experimental design involving one hundred and two students. The research instruments, a literary literacy test and a learning interest questionnaire, met validity and reliability requirements. The experimental group received treatment through a digital book-based Project-Based Learning (PjBL) model, while the control group received a digital book-based lecture model. Data obtained through the treatment and posttest were then analyzed using a two-way ANOVA in SPSS 27. The results showed a significant influence of the learning model and learning interest on children's literary literacy, as well as a significant interaction between the two. The PjBL model proved more effective than the lecture model, especially for students with high learning interest. The combination of a digital book-based Project-Based Learning (PjBL) model and high learning interest is the most effective strategy for improving literary literacy because it enriches the learning experience and fosters student independence and creativity. These findings imply the importance of integrating digital technology and a project-based approach in literature learning in elementary schools.